2007
DOI: 10.1590/s0100-29452007000200020
|View full text |Cite
|
Sign up to set email alerts
|

Características físicas, químicas e organolépticas de quipá (Tacinga inamoena, Cactaceae)

Abstract: RESUMO-A Opuntia ficus-indica tem-se destacado como principal produtora de frutos e forragens, motivo pelo qual tem sido bastante pesquisada. Além desta espécie, no semi-árido do Nordeste é encontrada a Tacinga inamoena, planta nativa, cujo fruto, embora também utilizado pelo agricultor como alternativa alimentar, não foi objeto de nenhuma pesquisa até o momento, justificando este trabalho para avaliar seu potencial nutricional e industrial, por meio das características organolépticas, químicas e físicas, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 5 publications
0
12
0
11
Order By: Relevance
“…However, different amounts have been reported for other cacti: 3.23 mg/100 g for pulp and 21.5 mg/100 g for the pericarp of Opuntia elatior (Alvarez et al, 2008), and 0.92 mg/100 g for Opuntia boldinghii (García-Pantaleón et al, 2009), showing that the values reported herein for T. inamoena fruit are quite lower. Souza et al (2007) reported a content of 0.47 mg/100 g for the pulp and 3.37 mg/100 g for the pericarp of the same species studied herein. In addition to the attractive coloring, carotenoids have high antioxidant capacity with strong health promotion appeal (Cayupán et al, 2011).…”
Section: Discussionmentioning
confidence: 49%
“…However, different amounts have been reported for other cacti: 3.23 mg/100 g for pulp and 21.5 mg/100 g for the pericarp of Opuntia elatior (Alvarez et al, 2008), and 0.92 mg/100 g for Opuntia boldinghii (García-Pantaleón et al, 2009), showing that the values reported herein for T. inamoena fruit are quite lower. Souza et al (2007) reported a content of 0.47 mg/100 g for the pulp and 3.37 mg/100 g for the pericarp of the same species studied herein. In addition to the attractive coloring, carotenoids have high antioxidant capacity with strong health promotion appeal (Cayupán et al, 2011).…”
Section: Discussionmentioning
confidence: 49%
“…Their physical, chemical and organoleptic characteristics are similar to those of Opuntia ficus-indica (Souza, Gamarra-Rojas, Andrade, & Guerra, 2007), species rich in vitamin C, calcium and magnesium, used in sweets, jellies, salads and ice cream (Van Wyk, 2005). For the mentioned similarities between T. inamoena and O. ficus-indica it is believed that the first can be used with the same purpose.…”
Section: T Inamoenamentioning
confidence: 94%
“…The mean pH value of the whole pulp was 5.59, which classifies it as a slightly acidic food, while the total titratable acidity of the pulp was, on average, 0.07% of citric acid, which is much lower than that reported by Souza et al (2007), 0.63%.…”
Section: Resultsmentioning
confidence: 60%